Divide and privatize: Firm break-up and performance - Evézen Koécenda; Jan Hanousek (Center for Economic Studies and ifo Institute (CESifo), 2011)
We analyze the long-term effects of firm break-up and ownership change on corporate performance. Our analysis is based on a unique data set for a large number of Czech firms spanning the period 1996-2005. We employ a propensity score matching procedure to deal with endogeneity problems. Our results, which are generally in line with the positive effects of firm break-up found in the developed-market literature, show that the initial effects of firm break-up are positive but after a certain point they quickly diminish over time. Factors like changes in ownership structure and management are to be found behind later improvements in the performance of firms.
Keywords: D23; G32; G34; L20; M21; P47; 330; break-up of firms; corporate performance; ownership changes; privatization; emerging markets; endogeneity; propensity score matching procedure; Desinvestition; Privatisierung; Unternehmensentwicklung; Aufstrebende Märkte; Schätzung; Tschechische Republik